2005
DOI: 10.1182/blood-2004-07-2814
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin modifies the hemochromatosis phenotype in mice

Abstract: Classic hereditary hemochromatosis (HH)is a common genetic disorder of iron metabolism caused by a mutation in the HFE gene. Whereas the prevalence of the mutation is very high, the clinical penetrance of the disease is low, suggesting that the HFE mutation is a necessary but not sufficient cause of clinical HH. Several candidate modifier genes have been proposed in mice and humans, including haptoglobin. Haptoglobin is the plasma protein with the highest binding affinity for hemoglobin. It delivers free plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Hemopexin seems to be required for this process because hemopexin-null mice show minimal heme loading in hepatocytes after heme overload (66). The observation that hemopexin-null mice, as well as haptoglobin-null mice, have normal hepatic non-heme iron levels suggests that heme iron uptake pathways are not significant contributors to hepatic iron stores under normal circumstances (82,83).…”
Section: Hepatocyte Iron Metabolismmentioning
confidence: 93%
“…Hemopexin seems to be required for this process because hemopexin-null mice show minimal heme loading in hepatocytes after heme overload (66). The observation that hemopexin-null mice, as well as haptoglobin-null mice, have normal hepatic non-heme iron levels suggests that heme iron uptake pathways are not significant contributors to hepatic iron stores under normal circumstances (82,83).…”
Section: Hepatocyte Iron Metabolismmentioning
confidence: 93%
“…5,6 Association studies between genetic markers and disease phenotype have given conflicting results. [7][8][9][10][11][12][13][14] More recently, candidate gene studies revealed significant associations between single nucleotide polymorphisms (SNPs) in genes involved in iron metabolism and indices of iron overload in p.C282Y homozygotes. Milet et al focused on two biologically relevant gene categories: genes involved in non-HFE-hereditary hemochromatosis (TFR2, HAMP, and SLC40A1) and genes involved in the regulation of hepcidin expression (BMP2, BMP4, HJV, SMAD1, 4 and 5, and IL6).…”
Section: Hfe-hereditarymentioning
confidence: 99%
“…The penetrance of hemochromatosis is a controversial issue 18,19 ; it is influenced by sex, age, environmental factors, and modifier genes. Studies of the identification of modifiers are promising in animal models, 20,21 but the identification of human modifiers remains complex.…”
Section: Primary or Genetic Iron Overload Hemochromatosismentioning
confidence: 99%